Masa Muda Masa Indah; Menghadapi Tantangan Bersama Tuhan - Hasahatan Hutahaean (EDULEAD: Journal of Christian Education and Leadership, 2021)
Coaching for young people is an investment in the future for a nation, religion, church, and also the future of the world of education. Neglect for the formation of youth means sowing the seeds of destruction in the future. On the one hand, although giving attention and coaching to young people regularly if the content of the coaching material is not based on essence truth and based on Bible truth, this will also result in a misguided future in the nation, religion, church as well as in the world of education. The consequences of that mistake would have to be paid dearly in the future. Therefore it can be said that errors in understanding result in errors in practice. This book gives serious attention to this field by presenting Bible facts ranging from ethics, Christian education to the use of internet media among young people. Understanding the contents of this book will provide true insight on how to give attention and guidance to young people for a bright futureAbstrakGereja memberikan perhatian pada pendidikan anak dan diwujudkan dalam bentuk pembinaan kategorial anak, pra-remaja, remaja dan dewasa. Hal ini bertujuan agar anak bertumbuh dalam kerohanian yang baik dan benar dan lebih takut pada Tuhan daripada takut pada sesama maupun falsafah hidup dunia yang tidak sesuai dengan pengajaran Alkitab. Buku ini memberikan panduan yang praktis dan mudah dimengerti bagi siapa saja yang terlibat dalam pembinaan kaum muda baik di Gereja maupun komunitas-komunitas dengan basis kaum muda. Penulis Buku biasanya menulis dengan memakai banyak contoh kasus yang telah ada, kemudian menggali Alkitab yang sesuai dengan topik sedang dibahas (studi kasus biasanya sampai 5 kasus), kemudian memberikan pengajaran yang menjadi pokok perhatian penulis. Ada enam belas topik yang dipaparkan penulis dalam buku ini dimana semuanya sangat penting dalam pendidikan agama kristen untuk kategorial anak hingga dewasa. Buku ini cocok untuk pemimpin yang memberikan perhatian dan upayanya untuk membentuk anak menjadi pemimpin masa depan yang tangguh.